Bemerkungen zu Catull C. 34 und 72 - Maurach, Gregor (Hyperboreus, 2013)
Catullus 34 and Horace, Odes 1, 21 have often been compared because of their thematic similarity (hymn to Diana resp. to Diana and Apollo), but the degree of inward participation has been overlooked. In Catullus c. 72 it has been underestimated how near the poet had come to a discovery of the indomitable unconscious.